Sh2-206: medio interestelar y formación estelar - Martín, María Cristina (2009)
The analysis of the interstellar matter around the HII region Sh2-206 shows extended emission in a region of more than 30 pc from the optical nebula detected both in the radio continuum and in the far IR. The distribution of dust, atomic and molecular gas, is compatible with the fact that the nebula is density bounded towards the east, and ionization bounded towards the south and west. This region is consistent with the champagne model.